Women's Empowerment and Public Policy in the Arab Gulf States Exploring Challenges and Opportunities - Naguib, Rabia; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2024)
This open access book explores the various dimensions of women$1 (Bs empowerment in public policy in the Gulf Cooperation Council (GCC), with a particular focus on Qatar, comparing the country to the other Gulf states. Through its rich compilation of empirical qualitative research, the text unpacks the various ways in which women$1 (Bs empowerment materializes in the GCC context, providing insights into public policy perspectives in high-income rentier states more broadly. The Arab world has long been part of the global dialogue on women$1 (Bs economic and political empowerment and the GCC has, over the past decade, situated women$1 (Bs empowerment amongst their respective national priorities and long-term strategies. In turn, the Gulf has seen gradual implementation of policies aimed at women, specifically, in looking to attract and retain them in the labour market, and in the public sector more broadly. The collection surveys and evaluates the progress made in recent decades, paying close attentionto the cultural and policy constraints still limiting women$1 (Bs empowerment in the Gulf. With a key linkage to SDG5, this book is a timely text addressing the context and drivers behind policies centering on women in the Arab region, in its analysis of the interplay of international women$1 (Bs empowerment discourse and regional public policy decisions. It is relevant to researchers and policy makers focused on women and gender issues in relation to social, cultural, economic, and political empowerment in the Gulf specifically, but also in the Arab world and beyond. .s
Chapter 1. Navigating Uncharted Waters: Women Empowerment and Public Policy in the Context of the Arab Gulf States -- Chapter 2. Grounded Approach to Women's Empowerment: Understanding the Complexities1 Rabia Naguib -- Chapter 3. A Maqasid Approach to Understanding Women$1 (Bs Status and Rights in Islam -- Chapter 4. Empowering Women Through Public Sector Employment: Challenges and Opportunities -- Chapter 5. Work-Life Balance Challenges and Family-Friendly Policies: Evidence from Qatar.s
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Sex; Political planning; Sociology; Social groups; Social legislation; Labor economics; Gender Studies; Public Policy; Sociology of Family, Youth and Aging; Labour Law/Social Law; Labor Economics